Evaluation of the quality and understanding of pregnant women and mothers in primary care in prenatal care (Research, Society and Development, 2021)
The objective is to present the importance of quality prenatal care, how this pregnant woman receives information and is received, and about the impact of information passed during this period. It is an integrative review study, of a qualitative nature, which broadly provides the knowledge and incorporation of the applicability of previous articles with subjects that present identical or related hypotheses. For data collection, keywords and some inclusion criteria were used, such as: having data collection that present the pregnant woman's vision during the puerperal pregnancy cycle and a study that has been carried out at the national level. As a result, we selected 14 articles related to the topic for the study and later classified into two categories: perception of pregnant women and / or puerperal women and quality of care. Even with some positive points, we conclude that the studies presented highlight that there is still a need for improvements in the strategy, promotion and health education in basic prenatal care so that we have effectiveness and adequate quality throughout Brazil. Therefore, there is no doubt that there is still a deficit in relation to the quality of care in Primary Health Care (PHC) for pregnant women and women who have recently given birth. For this reason, we suggest using current technology in our favor for incentive and also, conducting further studies and reviews with these scenarios.